تداعيات القرار الإسرائيلي بمقاضاة البنوك والاستيلاء على رواتب الأسرى الفلسطينين - عقل أحمد صلاح, محمد (University of Eloued جامعة الوادي, 2020)
لقد عمدت إسرائيل منذ عقود على استهداف الأسرى الفلسطينيين بكل الوسائل والسبل، فسنت عشرات القرارات ضد الأسرى، من أجل النيل منهم ومن إرادتهم وإظهارهم على المستوى الدولي كإرهابيين وليس كمناضلين من أجل قضيتهم العادلة وشطب عنهم صفة أسرى حرب. تتناول هذه الدراسة القانون الذي تم اتخاذه في أيار/مايو 2020، من قبل الكنيست الإسرائيلي والمتمثل في مصادرة أموال الأسرى ومقاضات البنوك الفلسطينية التي يتم من خلالها صرف رواتب الأسرى، وتسلط الدراسة الضوء على موقف السلطة الفلسطينية من هذا القرار، وآلية معالجتها للموضوع. Abstract: For decades, Israel has deliberately targeted Palestinian prisoners by all means and means. It has enacted dozens of laws against the prisoners, in order to undermine their will and show them on the international level as terrorists and not as fighters for the liberation of Palestine, and delete the status of prisoners of war from them. This study deals with the law that was passed in May 2020, by the Israeli Knesset, represented in the confiscation of prisoners' money and suing Palestinian banks through which the prisoners’ salaries are disbursed. The study sheds light on the Palestinian Authority’s position from the Israeli decision, And the mechanism for dealing with this decision
The repercussions of the Israeli decision to sue banks and seize the salaries of Palestinian prisoners
مقال
Keywords: السلطة الفلسطينية؛ إسرائيل؛ البنوك الفلسطينية؛ رواتب الأسرى؛ سلطة النقد الفلسطينية; Palestinian Authority; Israel; Palestinian banks; The salaries of prisoners; Palestinian Monetary Authority